2017
DOI: 10.1186/s41927-017-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

The underrated prevalence of depression in Japanese patients with rheumatoid arthritis - evidence from a Nationwide survey in Japan

Abstract: Background: To determine the prevalence of depression among Japanese people with rheumatoid arthritis (RA) and explore the relationships between depression and an array of variables. Methods: Nation-wide, cross-sectional online survey (n = 500) of people with RA including the Patient Health Questionnaire (PHQ-9) to measure the presence and severity of depressive symptoms were performed. Results: While only 5% of the population studied had been officially diagnosed with depression, 35% had PHQ-9 scores indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In our sample, 35% of patients were identified as suffering from either mild (24%) or severe (11%) depression. It has also been shown that depression in Japan often remains undiagnosed [50,51]. We found that while 89% of the patients in our Japanese sample of RA patients reported being satisfied with their current treatment, only 72% of those patients with severe depression were satisfied.…”
Section: Discussionmentioning
confidence: 47%
“…In our sample, 35% of patients were identified as suffering from either mild (24%) or severe (11%) depression. It has also been shown that depression in Japan often remains undiagnosed [50,51]. We found that while 89% of the patients in our Japanese sample of RA patients reported being satisfied with their current treatment, only 72% of those patients with severe depression were satisfied.…”
Section: Discussionmentioning
confidence: 47%
“…The PHQ-9 is a versatile self-reporting tool used for measurement of depression severity, diagnosis, as well as screening for the disease [19]. The study also found that among the RA population, younger patients, those affected by greater functional impairment, or patients on pain relief medications not biologic agents were more likely to experience depression [20]. Data from the Japanese IORRA registry also indicate that up to 41% of the RA patients were identified as depressed patients using a two-question screening tool [21], while a more recent study reported prevalence rates between 6.8 and 23.5% in depending on the tool that was used to determine depression [22].…”
Section: Discussionmentioning
confidence: 55%
“…Asian people are known to be reluctant to seek psychiatric treatment due to the stigma of mental illness 27 – 29 . In Japan, only 5% of the Japanese patients with rheumatoid arthritis had been diagnosed with depression, while 35% of the same population had PHQ-9 scores indicative of depression 30 . Increasing annual prevalence from 2002 to 2013 approaching the level of high-income western countries and decreased population with unmedicated depression (Fig.…”
Section: Discussionmentioning
confidence: 99%